Tinjauan Yuridis Tentang Kontrak KerjaKaryawan Pada Perusahaan Bergesen Worldwide Offshore - Ramadhan Syahputra Batara (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
Freedom of contract in this case can mean that someone is free to enter into an agreement, free of what is promised, and free to determine the form of the contract. Thus, it is expected that a fair and balanced contract will also appear for the parties. However, in practice there are still many standard contract models (standard contracts) that tend to be biased, unbalanced, and unjust.The problem in this thesis is: to know the procedure of work agreements at companies with Worldwide Offshore Bergesen Companies with employees and the position of PT. PP Equinox(shipping company) as a party listed in an employee employment contract, in an employee employment contract with a Worldwide Offshore Bergesen Companies.            The research conducted is empirical normative juridical, the source of data used to support this research is the source of secondary data and primary data obtained through field studies at Worldwide Offshore Bergesen Companies, an Indonesian limited liability company based in Gd. Midplaza I Lt. 9 Jl. Jend Sudirman Kav. 10-11, Karet Tengsin Tanah Abang, Central Jakarta, DKI Jakarta 10220 and BW JOKO TOLE FPU Ships located between Madura Island and Bali Island Indonesia.It was concluded that with the inclusion of PT. PP Equinox(shipping company) on employee employment contracts can confuse the status of the company PT. PP Equinox(shipping company) despite the fact that maybe Worldwide Offshore Bergesen Companies and PT. PP Equinox(shipping company) has an agreement, and can also create legal uncertainty against employees if there is a conflict between the company